The effect of core self-evaluations on career adaptability: The mediating role of protean career attitudes and the moderating role of meritocratic beliefs - Du, Bin; Yu, Xuan; Luo, Nan; Liu, Xuhong (Frontiers in Psychology, 2022)
Using the career construction model of adaptation as a guiding framework, we explored the impact of core self-evaluations on career adaptability among 1000 college students from China, with the mediating role of protean career attitudes and moderating role of meritocratic beliefs. The result of the survey showed that core self-evaluations positively predicted college students’ career adaptability; protean career attitudes mediated the relationship between core self-evaluations and career adaptability; meritocratic beliefs not only moderated the effect protean career attitudes have on career adaptability but also moderated the indirect influence of core self-evaluations on career adaptability through protean career attitudes. These results extend existing research about career adaptability and establish a new mediating mechanism and boundary conditions between core self-evaluations and college students’ career adaptability. In a word, we hope to develop career construction theory further.